Planning scenarios: preparing small retail custom furniture companies for a competitive futur (Revista de Administração, 2014)
In this work, a model of scenario construction to be used in small companies in custom furniture business is proposed; after its validity, this model could also be applied to other companies, considering their limitations. The proposed model was elaborated based on the ideas of taking into account the existing theories regarding the construction of scenarios as tools for the formulation of business strategies. To determine its validity, the model was applied to a small company of this sector, in which a qualitative research was performed and the methodological instruments used were documental research and brainstorming. Seven professionals from this field participated in the study. In the data selection, the model of was used, presenting the following variables: Climate Macro environment (inflation, financial incentives, world crises and legislation); Soil (increase of income and of Class C, habit changes and female work); Operational Environment (competition, trends, suppliers, technological evolution); and Internal Environment (values and personal aspirations, professional qualification). Based on the variables, two scenarios were elaborated for a period of time until mid-2018: a positive one, assuming favorable alterations for sales leverage, physical and financial growth of the organization; and a negative one, being unfavorable for the continuation and growth of the organization, which implies limitation of actions as a result of the market constraints. Finally, for each scenario, suggestions of strategies to be adopted by the company were elaborated. The use of the model showed its reliability based on the results found as well as its applicability, indicating that its proposal is viable.